Cases on public elementary school administration in the province of Samar - Cuenco, Arcadio M. 1928- (s.n.], 1965)
This study attempted to fill in the gap noted in current books and formal courses on elementary school administration and provided the empirical findings from which generalizations can be deduced on school administration. Moreover, the study presented some cases in the areas of policy, authority, and public relations in elementary school administration.